Delayed bubble, coil and trouble: young stroke as a presentation of paradoxical embolism from previously unrecognised pulmonary arterio-venous malformation (PAVM) - Trisha Singh; Jonathan Hinton; Rosie Swallow; James Kersey; Charles Hillier (Echo Research and Practice, 2020)
Young stroke patients should be investigated thoroughly to look for cardiac and extra-cardiac sources of emboli. We present a patient who was investigated for a cardiac source of emboli following an ischemic stroke. She was found to have a small patent foramen ovale (PFO), but due to the late appearances of bubbles on the bubble study it was thought that this was an incidental finding. Further investigation confirmed a PAVM was the source of emboli causing her stroke.